Characterisation of Serum Fibrinogen Degradation Products Using Gel Chromatography and Radioimmunoassay - Ratky, S. M; Sykes, A; Cooke, E. D; Gordon, Y. B (Thrombosis and Haemostasis, 1977)
Fibrin(ogen) degradation products (FDP) are detected by radioimmunoassay in the serum of all subjects. Some of these FDPs have considerable biological activity in vivo, and hence may play a significant part in the process of coagulation. Chromatography of serum samples from patients including those with pulmonary emboli and deep venous thrombosis indicates that the majority of non-clottable fibrin(ogen)-related antigen present is of high molecular weight- greater than that of fibrinogen – and that in pathological situations there is a quantitative increase not a qualitative alteration in the molecular species present.